Evaluation of the Hydrogeological Relationship between Monitoring and Production Boreholes in the Upper West Region. Ghana - Norgbe, B.Y. (University of Ghana, 1996)
To evaluate the hydrogeological relationship between monitoring and production boreholes in the Upper West region of Ghana, a total of 192 boreholes were studied. Out of these, 23 are monitoring boreholes and 169 are production boreholes. The types of aquifers being tapped by these boreholes have also been identified to determine the adequacy of the existing network of the monitoring boreholes. The region is underlain by basement complex rocks. The rocks are composed of granites, granodiorites and granite-gneisses. Metamorphosed volcanic. schists and phyllites of the Birimian formation occur along the western pollution of the study area. Three aquifer types were identified from geologic logs and drillers logs in the Upper West region. These are the weathered rock aquifers, the fractured unweathered rock aquifers and the fractured Quartz vein aquifers. These aquifers are inter-related and where they occur in combination with thick overburden, yields are enhanced in such boreholes. Statistical analysis; such as correlation and regression analyses were used to determine the relationship between the borehole properties, while the Theis (1935) Recovery and Cooper-Jacob (1946) methods were used to calculate the aquifer characteristics. There is a significant relationship between overburden thickness and yields in the study area. About ninety percent of the boreholes studied have overburden thicknesses exceeding 15m with yields of not less than 10 I/min. General}". yields range between 4.5 IImin. and 270 I/min in the 192 boreholes~. The mean and standard deviation are 25.4 I/min and 20.3 I/min respectively. Close values of the mean and standard deviation of the borehole yields indicate the heterogeneous nature of aquifers in the area. An average decline of 4.1 m in static water levels was observed in the region. This was attributed to reduced recharge:. low rainfall, high rates of evapotranspiration, increased surface run-off and excessive withdrawal of water from the boreholes. Transmissivity values computed using the Cooper-Jacob(l946) method ranges from 1.2 ml/day to log.2 mI /day in 47 boreholes. The mean and standard deviation values are 35.2 ml/day and 30.1 ml/day respectively. The closeness of these values, again explains the wide variations and extremity in transmissivity values of basement rock aquirers In the Upper-West region. The Theis(193S) Recovery method was used to compute the transmissivity values of six boreholes. The values range from 19.5 to 213.4 ml/day, while those calculated using the Cooper-Jacob (l946) solution technique from the same boreholes range between 24.5 and 183.4 ml/day. It was noted that more accurate transmissivity values were obtained rrom the Theis (1935) Recovery method than obtained from the Couper-Jacob (1946) method. Step-drawdown results used to calculate the borehole efficiencies of five boreholes after one hour of pumping indicate that none of the boreholes analyzed have inefficiencies exceeding 75% in the study area. Finally, the studies indicate that there exists virtually little or no hydrogeological relationship between ninety, percent of the monitoring; boreholes and the production boreholes; hence the 23 monitoring: boreholes established across the region are not adequately monitoring the groundwater levels of the area. They are also not representative of the production boreholes in the study area.
MPhil. Geology
Keywords: Hydrogeological; Upper West Region; Ghana; Boreholes